The Role of Marriage Guardian of the Same Clan in the Traditional Marriage of Batak Toba Muslims in Samosir Regency in the Perspective of Islamic Law - Ramadhan Syahmedi Siregar; Muhammad Syakban; Muhammad Ikhlas bin Rosele (Sharia Faculty of State Islamic University of Prof. K.H. Saifuddin Zuhri, Purwokerto, 2023)
A marriage guardian (wali) occupies a very important role in marrying the bride to the prospective groom. There is often a unique case found among the Batak Toba Muslims in Harian District, Samosir Regency in that the lineage of a marriage guardian is not clear (cannot be proven genetically). Thus, if a bride belongs to a Samosir clan, the leader of Samosir clan can be the marriage guardian for the bride as long as he is a Muslim. This study aims to see the implementation of traditional wedding ceremony in the Batak Toba Muslim community, to see some factors contributed to this phenomenon, and to see the role of a guardian in a traditional wedding ceremony of Batak Toba Muslim in the perspective of Islamic law. After analyzing the data, it was found that many cases of marriage involving guardian of the same clan but different lineage were triggered by little understanding of Islamic marriage. Therefore, the office of religious affairs is suggested to be more active in raising people’s awareness of the important roles of a marriage guardian. In addition, for people whose marriage guardian is not from the same lineage should register their marriage with a wali hakim as their marriage guardian.